Frameshift detection in prokaryotic genomic sequences. (29th July 2009) - Kislyuk, Andrey; Lomsadze, Alexandre; Lapidus, Alla L.; Borodovsky, Mark
We have developed a new method for frameshift detection, a combination of ab initio and alignment-based algorithms, that can serve as a useful tool for sequencing quality control in the next generation sequencing. We evaluated the method's accuracy on test sets of annotated genomic sequences with artificial frameshifts in protein coding regions. These tests have shown that the new method performs comparably to the earlier developed FrameD. On the sets of sequences produced by 454 pyrosequencing with sequence errors recovered by Sanger re-sequencing the accuracy of the method was shown to hold at the same level.